Design and Build Chatroom Application as Student Consultation Media Based on Android - Bastian, Alvian; Solihin, Muhammad Affiq; Irdan, Anggi Amelia; Jalal, Novita Maulidya (INTEK: Jurnal Penelitian, 2021)
To support the government’s program in preventing the spread of COVID-19 virus, it is expected to reduce direct communication between fellow students and lecturers. The purpose of this research to create interactive media that can provide consulting service for students with academic advisor (PA) without direct contact. It is expected for this research, students can be more proactive in interacting with their academic advisor in discussing academic and non-academic problems. The method used in this research is using Android Studio and Visual Studio Code as an Integrated Development Environment (IDE) and using a no-relational (NoSQL) realtime database on firebase. The advantage of this research is that the system to be developed does not use physical servers anymore but all databases are stored in the cloud system. The result of this research is chatroom application consisting of 7 modules namely application login with username and password, searching user, chatting user, list consultation, student input consultation, edit data consultation, and account setting.